2018
DOI: 10.3389/fmicb.2017.02624
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Skin Microbiota of the Cane Toad Rhinella cf. marina in Puerto Rico and Costa Rica

Abstract: Rhinella marina is a toad native to South America that has been introduced in the Antilles, likely carrying high loads of microorganisms, potentially impacting local community diversity. The amphibian skin is involved in pathogen defense and its microbiota has been relatively well studied, however, research focusing on the cane toad microbiota is lacking. We hypothesize that the skin microbial communities will differ between toads inhabiting different geographical regions in Central America and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
4
14
0
Order By: Relevance
“…Additionally, in our study, in every species with more than 4 amphibians sampled, the most abundant OTU was not the same in all of them. Both observations suggest that there are intraspecific variations in amphibian bacterial communities, these variations are possibly associated with environmental factors, presence of Bd or internal population variations of amphibian species, as has been reported by other studies ( Muletz et al, 2017 ; Abarca et al, 2018 ; Rebollar et al, 2018 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, in our study, in every species with more than 4 amphibians sampled, the most abundant OTU was not the same in all of them. Both observations suggest that there are intraspecific variations in amphibian bacterial communities, these variations are possibly associated with environmental factors, presence of Bd or internal population variations of amphibian species, as has been reported by other studies ( Muletz et al, 2017 ; Abarca et al, 2018 ; Rebollar et al, 2018 ).…”
Section: Discussionsupporting
confidence: 79%
“…More recently, it has been suggested that environmental factors may also play an important role in the variation of the amphibian bacterial microbiota ( Muletz et al, 2017 ; Bird et al, 2018 ; Varela et al, 2018 ). It has also been reported that bacterial communities can vary according to geography ( Abarca et al, 2018 ; Rebollar et al, 2018 ), ecomorphs ( Bletz et al, 2017a ) and ontogeny ( Longo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the synthesis of these compounds may involve different biosynthesis pathways, which may be selectively accessed in different environmental conditions. Some studies have indicated that bufogenins may also be transformed by certain microorganisms 33,34 , and the correlations between different chemical components may result from biotransformation of the toad skin microbiome in different habits.…”
Section: Discussionmentioning
confidence: 99%
“…As the mixed defensive toxins were obtained from different adult toads at each geographical site, this regular pattern of chemical defence phenotypic plasticity induced by geographical factors was not related to the gender, age, or size of the individual toads. Although predators and competitors in different regions may have certain effects on the variation in defensive toxin production 8,12,34 , the density and type of these species in different regions vary greatly 7,34,35 . Accordingly, we conclude that this regular variation in geographical environment was not mainly induced by the presence of these species.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus is often used as a probiotic on farms to prevent disease; therefore, the high abundance of Firmicutes in the farmed group may depend on human factors. Bacteroidetes and Firmicutes are predominant bacteria on the skin of many amphibians (Abarca et al 2017;Bates et al 2018). The relative abundances of the phyla Proteobacteria, Bacteroidetes, Firmicutes and Actinobacteria in the two groups were significantly different, both of which belonged to the phylumlevel in LDA.…”
Section: Discussionmentioning
confidence: 98%